Drip irrigation of plastic mulched strawberry using carbonated water - a greenhouse study - Shore, Margaret L. (Colorado State University. Libraries, 2023)
1994 Fall. Covers not scanned. Includes bibliographical references. Carbonated water irrigation enhanced yields of tomato, however, little is known about the mechanism of this response. Objectives were: 1.) determine if strawberry responds to irrigation with carbonated water and 2.) determine if yield increase, should it occur, is due to short-term soil pH optimization or air-soil atmospheric enrichment with CO2. Two different soils (2:1, perlite:soil) were used: a calcareous soil (5% CaCO3, pH 8.0), with a Zn content of 0.9 μg/g and a non-calcareous soil (< 1 % CaCO3, pH 6.4) with a Zn content of 8.4 μg/g. The carbonated water temporarily lowered the pH of the calcareous soil to 6.7 and the non-calcareous soil to 5.9, at both extremes of the optimal range (5.2-6.4) for strawberry. There was significant increase in above ground (1 cm) CO2 during irrigation. Also, a significant increase in soil CO2 was observed in the calcareous soil, carbonated water treatment over the noncalcareous, carbonated water treatment, which suggests carbonic acid played a role in lowering the surface pH of the calcareous soil from 8.0 to 6.7 shortly after each irrigation event. Application of carbonated water increased production of buds and open flowers at the P < 0.05 significance level. Carbonated water increased the production of marketable fruit (P < 0.10) as compared to the noncarbonated water considering both soils. In addition, there was greater crown dry weight and higher leaf chlorophyll content (P < 0.05) observed in plants irrigated with carbonated water. The magnitude of the response to carbonated water was similar for each soil. The noncalcareous soil had significantly greater accumulation of Zn in leaf tissue as compared to calcareous soil, considering both irrigation treatments. However, the calcareous soil, carbonated water irrigation treatment had a slight increase in the uptake of Zn over the calcareous, noncarbonated water treatment. Also, there was no significant difference in the uptake of Fe, ...